Differentiating postmortem claw marks by the Asian water monitor (kabaragoya) from antemortem sharp weapon trauma based on the injury pattern - Piumi Dileka; Chiranthika Madhupoorni A. Gunathilaka; Thilinika Ranchamali; Sameera A Gunawardena (Wolters Kluwer Medknow Publications, 2022)
The Asian water monitor (Varanus salvator) or kabaragoya is the predominant large animal scavenger of human remains in Sri Lanka; however, its significance is rarely discussed in the forensic literature. This is the case of a 54-year-old male with a history of dementia, depression, and wandering behavior whose body was found, partially submerged in a river, 2 days after he was reported missing. There were several linear wounds with regular margins over his arms and face which raised the suspicion of homicidal sharp weapon trauma. The injuries were seen in clusters and did not involve harder structures such as tendons, ligaments, or bones. There were no signs of inflammation or bleeding. They were attributed to kabaragoya claw marks, which are postmortem artifacts that mimic incised wounds. However, there were no areas of tissue loss to indicate that the animal had begun feeding on the corpse. This case discusses the problems faced by medicolegal investigators when encountering this phenomenon which is relatively underreported in the forensic literature.